Age-related changes in Asian elephants' estrous cycle - Hiltunen, Ilpo (My University, 2024)
Reproductive senescence is recognized across species, but only a small number of them have a clear physiological reproductive cessation (i.e. menopause) and long post-reproductive lifespan. In female mammals, the reproductive ability is determined by the menstrual or estrous cycles and the associated hormones that prepare females for reproduction. Along with other factors, aging and reproductive history can cause changes in the qualities and prevalence of estrous cycle affecting fertility rates. Demographic data from long-lived Asian elephants has shown that female individuals of the species have relatively long post-reproductive lifespan although some of them are capable of reproducing beyond 60 years of age. However, the physiological processes and estrous cycle characteristics have not previously been investigated in Asian elephants. The aim of this thesis is to study how age, recent reproduction and some other key factors affect the estrous cycle characteristics in semi-captive Asian elephants to gain knowledge on the possible reasons for reproductive termination in the species. Estrous cycle profiles were determined for 69 Asian elephants by measuring and analysing their serum concentrations of a progesterone metabolite, allopregnanolone. Based on cyclicity patterns, elephants were categorized to cycling and non-cycling individuals. Statistical models investigated how age, recent reproduction and additional factors affect the elephants’ 1) mean allopregnanolone concentrations, 2) probability of having an estrus cycle and 3) cycle length. The results showed that age was not associated with mean allopregnanolone or cycle length. However, middle-aged elephants (~30-50 years old) had a higher probability of cyclicity than the younger (9-30 years old) and older (50-71 years old) elephants. Recent reproduction was not associated with mean allopregnanolone or cyclicity, but there was weak yet non-significant evidence on recent reproduction increasing cycle length. In this thesis, Asian elephant’s estrous cycle was investigated for the first time in the species’ natural living environment and with a larger sample size. The observed age-related changes in estrous cyclicity were not as comprehensive as in truly menopausal species, but can be indicative of individual level menopause in some Asian elephants. As the demographic characteristics of the studied semi-captive elephants resemble more closely those of wild elephants than the elephants in zoos, the acquired information on how age and reproductive history affect the elephants’ estrous cycle provides new insights that are relevant for the future research that investigates how evolution has shaped the species’ physiology and reproductive lifespan. This thesis also gives new insights on the reproductive senescence patterns in long-lived animals in general, which is useful for the research of these species as individual-level physiological data is often very limited, particularly on animals living in their natural habitats.
Keywords: elephants, estrous cycle, allopregnanolone, age, reproductive senescence